Pendidikan Demokrasi dalam Perspektif Filsafat Pendidikan Islam - AG, Turham (Jurnal Pendidikan Indonesia, 2021)
Democracy is a must to be practiced in the educational process. As an instrument of glue and unification of the nation at the practical level, education must accommodate broadly democratic principles, the Prophet has set a good example for us, in practice democracy cannot be separated from discussion and dialogue, so that students are not educated to be good at memorizing things. but rather to assess, evaluate critically and be taught how to examine problems and how to understand them. So it is hoped that Islamic education can implement the concept of democracy that is appropriate and in accordance with the goals and philosophy of Islamic education to improve the quality of educational services with quality insight so that it will be able to survive in accordance with the needs of the community without losing the main purpose of Islamic education.